Digital assessment formats in higher education: an empirical analysis of the process efficiency of e-assessments compared to paper-pen exams - Flavio Di Giusto (International Journal of Evaluation and Research in Education (IJERE), 2026)
Digitalization is reshaping higher education, including the way examinations are designed and administered. Electronic assessments (EA) are widely regarded as promising tools to enhance process efficiency. This article presents the findings of a mixed-methods study conducted at Zurich University of Applied Sciences (ZHAW), comparing traditional paper-pen exams (PPE) and EA across both multiple-choice (MC) and open-question (OQ) formats. Using a process cost analysis across three modules (n>700), supported by interviews and student surveys, the study investigates time, cost, and acceptance outcomes. Results show that EA with MC formats yield substantial efficiency gains—reducing overall costs by up to 85%—primarily due to automation in grading and archiving. However, for OQ formats, digitalization provides only marginal cost benefits, as manual grading remains a major cost driver. The study offers nuanced insights into the process dynamics of digital exams and emphasizes that the economic advantages of EA strongly depend on exam format and institutional implementation strategies.